PENGARUH KETERSEDIAAN BARANG DAN KECEPATAN PENGIRIMAN TERHADAP KEPUASAN PELANGGAN - Bramasta, Adjie; Ikram, Abdi Dzil (Jurnal Kewirausahaan dan Inovasi, 2023)
The objective of this research is to identify the effect of goods availability and delivery speed on customer satisfaction. The sample of this quantitative research is 130 customers of CV Favorite, a mineral water distributor company in Trenggalek, who were selected using simple random sampling. The data was harvested from questionnaires provided online and offline when the respondents were making transaction at the store. The results of the multiple linear regression analysis indicate that goods availability and delivery speed significantly affect customer satisfaction. Therefore, CV Favorite is suggested to maintain or increase the values of goods availability and delivery speed, so the company is able to keep or enhance the satisfaction  of its customers.